321 Back Pain in Surgically Treated Degenerative Lumbar Spondylolisthesis: What Can We Tell Our Patients. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Bond, Michael; Zhou, Hanbing; Dea, Nicolas; Bailey, Christopher; Charest-Morin, Raphaele; Glennie, Andrew; Manson, Neil; Hall, Hamilton; Thomas, Kenneth; Rampersaud, Y. Raja; McIntosh, Greg; Fisher, Charles
Abstract: INTRODUCTION: Surgery for degenerative lumbar spondylolisthesis (DLS) has traditionally been indicated for patients with neurogenic claudication. Surgery improves patients' disability and lower extremity symptoms, but less is known about the impact on back pain. This study aims to evaluate changes in back pain after surgery and identify prognostic factors influencing these changes in surgically treated DLS. METHODS: Consecutive patients with DLS surgically treated were prospectively enrolled in the Canadian Spine Outcomes Research Network (CSORN) registry. Patients had demographic data, clinical information, disability (Oswestry Disability Index), and back pain (Numerical Rating Scale back pain) scores collected prospectively at baseline, 3, 12, and 24-mo follow-up. Results were compared to baseline using simple summary statistics and factors associated with improved back pain were assessed with multivariate regression (significance was P < .05). RESULTS: A total of 557 patients were identified, all had reached 3-mo follow-up, 376 (67.5%) had reached 12-mo follow-up, and 141 (25.3%) had reached 24-mo follow-up. Mean age at baseline was 66.2 (± 9.5), and 58.5% were female. Back pain improved significantly at 3 mo, and was maintained at 12 and 24-mo follow-up compared to baseline ( P < .001). Improvement in NRS back pain scores at 12 mo was on average 3.2 (±2.8) points and clinically significant improvement in back pain was observed in 75% of patients (MCID NRS pain 2 points). Factors associated with worse back pain scores at 12-mo follow-up were higher baseline back pain, worse baseline physical function, at least 1 adverse postoperative event, and longer duration of symptoms ( P < .05). CONCLUSION: Back pain improved significantly during follow-up for patients treated surgically for DLS. This research demonstrates that for patients undergoing surgery for DLS, the majority will have improved back pain at 1-yr follow-up.